Hepatitis B vaccines - Yu, Andy S; Cheung, Ramsey C; Keeffe, Emmet B (Infectious disease clinics of North America, 2006)
Immunization is the most effective way to prevent transmission of HBV and, hence, the development of acute or chronic hepatitis B. The national strategy to eliminate transmission of the virus in the United States includes vaccination of all newborn infants, children, adolescents, and high-risk adults. Postexposure prophylaxis is also advocated, depending on the vaccination and anti-HBs status of the exposed person. Seroprotection after vaccination, defined as anti-HBs > or = 10 mIU/mL, is achieved in over 95% of all vaccinees. The hepatitis B vaccines are very well tolerated with usually minimal adverse effects. Predictors of non-response include increasing age, male gender, obesity, tobacco smoking, and immunocompromising chronic dis-ease. For those who remain nonresponders after the second series of vaccination, adjuvants such as GM-CSF may be considered, but their results are variable.